Gender-Based Violence in a Migration Context: Health Impacts and Barriers to Healthcare Access and Help Seeking for Migrant and Refugee Women in Canada - Evangelia Tastsoglou (Societies)
This article focuses on the health impacts of the gender-based violence (GBV) experienced by migrant and refugee women (MRW) survivors in their migration/settlement journeys in Canada, and their challenges in accessing healthcare. Adopting a feminist and intersectional lens, I draw upon qualitative in-depth interviews with 48 migrant women conducted between 2020 and 2022. GBV is a frequent experience in the migration and (re)settlement journey and has wide-ranging and cross-secting emotional-psychological, socio-economic, physical, as well as sexual and reproductive health consequences which, in turn, impact settlement and integration and may increase vulnerability to further GBV as a result. Drawing upon a “social determinants of health” approach, I aim to understand the workings of barriers to healthcare access and help seeking for MRW survivors of GBV in Canada. The social determinants of health involve structural (e.g., legal, financial, linguistic, knowledge, healthcare access) barriers, mediated by gender, intersecting with various positionalities and identities. GBV unambiguously impacts on the health and well-being of all survivors, but the extent of harm varies significantly depending on the intersections of positions and identities of survivors. The migration context entails unique barriers to MRW help seeking and healthcare access as well as aggravates the impacts of other barriers on MRW. My objective is to show how GBV affects the health status of MRW survivors in Canada in the specific context of healthcare access and help-seeking barriers MRW face, conceptualized as risk factors for reproducing GBV.